Distinctive roles of PLD signaling elicited by oxidative stress in synaptic endings from adult and aged rats - Mateos, Melina Valeria (2012)
The role of iron in oxidative injury in the nervous system has been extensively described. However, little is known about the role of lipid signal transduction in neurodegeneration processes triggered by iron overload. The purpose of this work was to characterize the regulation and the crosstalk between phosphatidylcholine (PC)-derived diacylglycerol (DAG) and cannonical signaling pathways during iron-induced oxidative stress in cerebral cortex synaptic endings (Syn) obtained from adult (4 months old) and aged (28 months old) rats. DAG production was increased in Syn exposed to iron. This rise in DAG formation was due to phospholipase D1 (PLD1) and PLD2 activations. In adult rats, PKD1, ERK1/2 and PKCα/βII activations were PLD1 and PLD2 dependent. In contrast, in senile rats, DAG formation catalyzed by PLDs did not participate in PKD1, ERK1/2 and PKCα/βII regulations, but it was dependent on ERK and PKC activities. Iron-induced oxidative stress promoted an increased localization of PLD1 in membrane rafts, whereas PLD2 was excluded from these domains and appeared to be involved in glutamate transporter function. Our results show a differential regulation and synaptic function of DAG generated by PLDs during iron-induced oxidative stress as a consequence of aging.